The emerging roles of aberrant alternative splicing in glioma - Reda Ben Mrid; Sara El Guendouzi; Marco Mineo; Rachid El Fatimy (Cell Death Discovery, 2025)
Abstract Gliomas represent a heterogeneous group of uniformly fatal brain tumors. Low and high-grade gliomas have diverse molecular signatures. Despite successful advances in understanding glioma, several genetic, epigenetic, and post-transcriptional alterations leave various targeted therapies ineffective, leading to a poor prognosis for high-grade glioma. Recent advances have revealed the implication of dysregulated alternative splicing (AS) events in glioma development. AS is a process that produces, from a single genomic sequence, several mature messenger RNAs. Splicing of pre-messenger RNAs concerns at least 95% of transcripts and constitutes an important mechanism in gene expression regulation. Dysregulation of this process, through variations in spliceosome components, aberrant splicing factors and RNA-binding protein activity, disproportionate regulation of non-coding RNAs, and abnormal mRNA methylation, can contribute to the disruption of AS. Such disruptions are usually associated with the development of several cancers, including glioma. Consequently, AS constitutes a key regulatory mechanism that could serve as a target for future therapies. In this review, we explore how AS events, spliceosome components, and their regulatory mechanisms play a critical role in glioma development, highlighting their potential as targets for innovative therapeutic strategies against this challenging cancer.